Variational Analysis Down Under Open Problem Session - Bui, Hoa; Lindstrom, S.B.; Roshchina, V. (Springer, 2019)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. We state the problems discussed in the open problem session at Variational Analysis Down Under conference held in honour of Prof. Asen Dontchev on 19–21 February 2018 at Federation University Australia.